International Legal Consequences of the Construction of a Barrier by Israel in the West Bank - Golnitz, Hinnerk (School For Advanced Legal Studies, 2023)
At the 10th emergency special Session on December 8, 2003, the 191-member United Nations General Assembly adopted a resolution requesting an 'urgent' advisory opinion from the International Court of Justice in The Hague on the legal consequences of Israel's construction of a 'Barrier' between itself and the West Bank and East Jerusalem. 1 The Secretary General of the United Nations transmitted the request for the advisory opinion to the Court in a letter dated December 8, 2003. The Assembly has requested advisory opinions from the Court fourteen times since the Court's inception in 1946, with the majority requested immediately following World War 11. While the Court's opinion is not legally binding, the opinion provides strong guidance to both parties, as well as the international community, on how to treat the current situation and how to proceed with negotiations.